Body-composition profile of Argentine tennis players - Puerta, H.; Maquirriain, J.; Aquilino, G.; Cardey, M.; Guillone, C.; Diaz, I.; Lentini, N.; Rodriguez-Papini, H. (2002)
Anthropometrics and body composition are relevant factors in sports performance. The aim of this retrospective study was to profile such morphological features in Argentine competitive tennis players. Anthropometric and body-composition data were recorded from 189 competitive tennis players from January 1992 to March 1999. Records included age, weight, height, skin folds, limb circumferences, bone width, body composition (5 components by Kerr's method) and somatotype (by Heath-Carter's method). Collected data were classified according to sex and chronological age.